Éléments D’interprétation En Droit Civil - Lemieux, Charlotte (Revue de droit de l'Université de Sherbrooke, 1994)
This article reviews the methods, rules and sources of interpretation relating to Quebec Civil Law. While the Civil Law utilizes many generally accepted interpretive methods and directives, it does so idiosyncratically. These distinctive applications, both methodological and fundamental, derive not only from the nature of the Civil Law itself but also from the process of codification. The writer insists that one should not lose sight of this fact when interpreting the new Civil Code.